The ring of Solomon - Stroud, Jonathan (Stroud, Jonathan. Bartimaeus trilogy, 2010)
Wise-cracking djinni Bartimaeus finds himself at the court of King Solomon with an unpleasant master, a sinister servant, and King Solomon's magic ring